Representasi Indonesia dalam Stand Up Comedy (Analisis Wacana Kritis Norman Fairclough dalam Pertunjukan Spesial Pandji Pragiwaksono “Mesakke Bangsaku”) - Angger Siswanto; Poppy Febriana (Kanal: Jurnal Ilmu Komunikasi, 2017)
The purpose of this research exposes the representation of Indonesia through a good comic material delivered by Pandji Pragiwaksono in a special performance "Mesakke Bangsaku". This research uses descriptive method using a literature review and observations in order to enrich the data. Data analysis techniques used for this research is a critical discourse analysis of Norman Fairclough, which includes Text, Discourse Practice, Sociocultural Practice. The results showed the existence of the findings regarding the representation of Indonesia which is described through the stand up comedy Special in the show " Mesakke Bangsaku", Pandji Pragiwaksono. First, regarding representation of society Indonesia that are valued can do attitude of tolerance towards religious people. Second, Indonesia is still very much need to learn from the educational system in the developed world, and the third is about a political understanding that is still very weak.